HUBUNGAN ANTARA KADAR NITROGEN OKSIDA DENGAN JUMLAH PENDERITA ISPA DI SEKITAR LAPINDO - Emy Tri Handayani; Suroso Bambang Eko Warno; Musta'in . (Poltekkes Kemenkes Surabaya, 2013)
The emerging mud volcano known as Lumpur Lapindo Sidoarjo represents a significant disaster inducedby industrial activities. One of the immediate impacts caused by Lumpur Lapindo in Porong area is air polutionsuch NOx• Such polution may affect human health namely the upper respiratory disturbances known as [SPA.This study was directed at surveying existing temperature and humidity, wind velocity and direction, dischargeof NOxgas, ambient air and to enumerate people suffering from ISPA in PuskesmasJabon and Porong, toestablish an association between NOxconcentration around Lumpur Lapindo site with the increasing numberof people suffering from ISPA.This study was driven as a cross-sectional descriptive exercise. Data were collected on air temperatureand humidity, wind velocity and direction, discharge of NOxto be entered into descriptive analyses.The survey resulted in air temperature of 31.1DC,humidity 62.4 %, wind velocity of 2.89 m/s and a windderection from the north to south. The chemical parameter in the survey was NOx gas in ambient air of 24.7IJg/Nm3 which was still below the designated ambent air quality standard in the Per.GubJatim No. 10 Tahun2009. Records indicated that the number of people suffering from ISPA have been increasing since 2006 2012.This did not have any relationship with the NOxsituation, instead it may be caused by other factors.The suggestion offered to BPLSwas for it to keep going green and for its workers to wear masks. ThePuskesmaswas encouraged to do something about the ISPA patients. The community were encouraged toplant shrubberies and trees to create green environment and to keep in touch with the Puskesmas.Keywords : Gas NOx,upper respiratory disorder, Saltzma